The Meaning of Taqnathu in the Qur'an: A Semantic Analysis by Toshihiko Izutsu - Anifa Rifka Hanna; Ahmad Nurrohim (al-Afkar, Journal For Islamic Studies, 2026)
Taqnathu is one of the words in the Qur'an to mention the term despair. This discussion is interesting to study more deeply considering that in this day and age it shows an increasing sense of despair when facing complex life pressures that eventually lead to depression and pessimism about the future. This study aims to analyze the meaning of taqnathu in the perspective of the Qur'an using the semantic approach of Toshihiko Izutsu. The research method used is qualitative with the type of library research and data collection techniques are carried out through documentation studies on the verses that contain the words. The data sources used are divided into primary data in the form of verses of the Qur'an and secondary data in the form of tafsir books, Arabic lexicography dictionaries, books, and scientific journals related to the semantics and meaning of taqnathu. The results of this study show that: first, the word taqnathu in the Qur'an has several derivations, such as yaqnathu, qanathu, qanuth, yaqnathun, and qanithin. Second, the relational meaning, syntagmatically the word taqnathu in the Qur'an has several meanings related to the condition of despair in various contexts, such as the characteristics of a perverted, the loss of hope after a disaster, to the prohibition of despair from the mercy of Allah. Paradigmatically speaking, this word has synonyms with ya'isa, istay'asa, and ablasa, and is antonymmy with istaqāmu, istibsyār, and yastabsyirun. Third, historically, the meaning of taqnathu has evolved from the concept of despair in the pre-Qur'anic tradition, then deepened theologically in the Qur'an in the Qur'anic period, to the post-Qur'anic period which emphasizes the aspect of Allah's compassion and forgiveness in the interpretation of scholars.